(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Solar energy as a source of electric power is gaining traction in Brazil, and it is the topic of global environmental debates. Electric energy, which is a right of all people, represents a large-scale use of natural resources. In 2016, state schools in Paraná spent more over R 46 million to provide power and therefore provide the system with necessary operating conditions. 15 schools in Curitiba/"Regional PR’s Administrative do Cajuru" were assessed in terms of electric energy usage and expenditures from January to May 2017, and a solar photovoltaic system was dimensioned to meet each school’s need. It was calculated that the entire savings from the energy that would no longer be spent on power could be allocated to other educational programs and community-oriented initiatives to help the school achieve sustainability. The projected yearly savings were more than R 435 thousand.